Implementasi Multi - Channel Pada Wireless Sensor Network - Ariyan Jazmi; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wireless Sensor Network is a technology used in obtaining data from physical conditions or environmental conditions with the help of sensors. Wireless Sensor Network consists of several nodes that will transmit data on the Gateway node. Wireless Sensor Network communication requires the same Channel to connect between nodes. Problems with the Wireless Sensor Network if the area is monitored widely and the nodehas multi- channels will require a lot of Gateway nodes according to the number of channels. Wireless Sensor Network communication like this is less concise and requires extra funds. Based on the problems mentioned in this research applied Wireless Sensor Network communication with multi-channel. Multi-channel will improve the performance of data transmission so that on the Gateway nodethere are several channels for communication with the node. The method in this study is another SPI (Serial Periperal Interface) on the node, I2C on the Gateway node. The results of Wireless Sensor Network communication with Multi-Channel method can improve the delivery and data reception performance. The node address specification has an important role in multi-channel communication to perform channel switches in receiving data on the server. Data obtained by the server successfully received at the same time, but it takes approximately 2 - 4 seconds of synchronization at the beginning communication.